Implementasi Algoritma Kruskal untuk Menentukan Minimum Spanning Tree Rute Tempat Pembuangan Sampah Berbasis GUI - Moch. Anang Karyawan; Yusuf Effendi; Muhammad Zakariya Alif Ridwan; Maulana Muhammad Adityawarman; Muhammad Khairul Ikhwan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Waste management in urban areas such as Surabaya faces dual challenges of increasing waste volume and operational efficiency. The city’s daily waste production of approximately 1,800 tons requires a precise logistics system to reduce transportation costs, which account for 60% to 85% of the total municipal waste management budget. This study aims to optimize waste collection routes in East Surabaya, a rapidly growing area. Kruskal’s algorithm was implemented to determine the Minimum Spanning Tree (MST) of the waste disposal network. The Waterfall software development model was applied to build a Java-based Graphical User Interface (GUI) application that visualizes optimal routes with minimal total distance. Distance data among six waste disposal sites (TPS) were obtained from actual road mapping and modeled as a weighted graph. The selection of only six TPS was intended as a case study to simplify the initial modeling process, which presents certain limitations in generalization but remains relevant for demonstrating route optimization potential. The results show that Kruskal’s algorithm produced an MST structure with a minimum total distance of 11 km. The developed application was tested and proved effective in supporting route planning and providing user-friendly graphical visualization. This research is expected to contribute to decision-making in optimizing urban waste collection logistics.